Hot machining of hardened steels with coated carbide inserts - Lajis, Mohd Amri; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Che Daud, Mohd Radzi; Ginta, Turnad Lenggo (Science Publications, 2009)
Problem statement: The benefits of easier manufacture of hardened steel components can be substantial in terms of reduced machining costs and lead times compared to the traditional route involving machining of the annealed state followed by heat treatment, grinding/EDM and manual finishing. But machinability of hard material through conventional machining is hindered due to excessive wear of the cutting tools and differently in achieving desired quality of the machined surface. In end milling the cutting tool is not in constant operation and so undergoes a heat cycle during the intermittent cutting. This alternate heating and cooling of the inserts lead to the thermal cracks and subsequently failure of the tool.